Formation of motivation of older generation citizens for active longevity by means of adaptive physical culture - Evseeva O.E. ,; Ladygina E.B. ,; Evseev S.P. ,; Shelekhov A.A. ,; Aksenov A.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to scientific substantiation of proposals for the use of adaptive physical culture means to create motivation for active longevity in older citizens (taking into account sensory, motor and mental disorders). Methods and structure of the study. To obtain the necessary information, an analysis of documentary materials and literary data on the current state of the problem of motivation for active aging among older citizens in the Russian Federation was used. In addition, the level of motivation among older citizens to engage in physical education was monitored. Results and conclusions. Studying the problem of developing motivation among older citizens (taking into account sensory, motor and mental disorders) for active longevity using pedagogical means of adaptive physical culture involves the use of an interdisciplinary approach that takes into account pedagogical, sociological, psychological, physiological and other aspects of this process. The need for a multidimensional study of issues related to the formation of motivation among representatives of older age groups of the population for systematic physical education and sports, stated in the study, is due to the high heterogeneity of the studied population - elderly people of various nosological and age groups, the variability of spheres and social institutions that implement work in the interests of elderly citizens.